Model Pengembangan Nilai Agama Islam pada Siswa Slow Learner untuk Penguatan Moderasi Beragama - Almaydza Pratama Abnisa; Zubairi Zubairi; Lutfia Nursanti (Social Science Academic, 2026)
This research aims to develop an effective learning model for instilling Islamic religious values, particularly those related to religious moderation, in slow-learning students in inclusive schools. Slow-learning students require an adaptive and structured instructional approach to understand abstract concepts such as religious moderation.The model developed integrates a visual-kinesthetic approach, experiential learning, and the use of interactive digital media, adapted to their learning characteristics. The trial results showed a significant increase in students' understanding and moderate attitudes toward diversity. This model is recommended as a practical guide for Islamic Religious Education (PAI) teachers in supporting inclusive education and strengthening national character.